From Safety Culture to Procedural Discipline: A Multistage Model of Compliance Behavior in Aviation Training Environments - Ahmad Bahrawi; Dhian Supardam; Dani Chandra Yudho Pranoto; Hadi Prayitno; Fiel Salvador Rangel Da Cunha Braz (Langit Biru: Jurnal Ilmiah Aviasi, 2026)
Procedural compliance is a critical determinant of operational safety in aviation, where deviations from Standard Operating Procedures (SOPs) may escalate into serious safety risks. This study examines how organizational safety culture influences SOP compliance among aviation trainees through instructor safety practices and the internalization of safety values. Using the Safety Culture–Compliance Behavior (SCCB) framework, the study integrates organizational, instructional, and psychological perspectives. A cross-sectional survey of 275 aviation trainees was analyzed using reliability testing, correlation analysis, multiple regression, and serial mediation modeling. The results show that organizational safety culture significantly predicts instructor safety practices, instructor practices strongly influence safety internalization, and safety internalization is the strongest predictor of SOP compliance. Serial mediation analysis confirms that safety culture influences compliance primarily through the sequential pathway of instructor practices and safety internalization. These findings highlight the importance of instructor-centered safety leadership and training strategies that foster psychological commitment to safety.